Physiological Properties of Dietary Ellagitannin-Rich Preparations Obtained from Strawberry Pomace Using Different Extraction Methods - Juśkiewicz Jerzy; Król Bogusław; Kosmala Monika; Milala Joanna; Zduńczyk Zenon; Żary-Sikorska Ewa (Polish Journal of Food and Nutrition Sciences)
The objective of this study was to establish the composition of strawberry preparations rich in ellagitannins obtained using water or acetone extraction (EF and EP preparation, respectively). Then, biological effect of these extracts was assessed in 4-wk nutritional experiment on Wistar rats. The preparations were applied in cholesterol-containing diets that had equal content of ellagitannins (0.03%). To measure animals response, parameters describing the caecal fermentation (ammonia and short-chain fatty acid concentrations, bacterial enzymes activity), blood serum lipoprotein profile, and TBARS content in selected tissues (heart, liver, kidney) were assessed. Apart from polyphenols, including ellagitannins (7.8 and 7.1%, respectively), the EF preparation contained high quantities of soluble dietary fibre and other carbohydrates (33.3 and 38.9%, respectively), whereas the EP preparation was characterised by 58.9% content of ellagitannins, no dietary fibre and a high content of proanthocyanidins (16.9%). In comparison to EF group, the dietary treatment with EP had a stronger effect on caecal environment as manifested by decreased digesta bulk, β-glucuronidase activity and total short-chain fatty acid concentration (P<0.05 vs. group C without supplementation). Both preparations lowered lipaemia and glycaemia. It could be concluded that more efficient acetone extraction of strawberry pomace increased the content of both ellagitannins and proanthocyanidins in the polyphenolic preparation, which caused a stronger inhibiting effect on caecal fermentation processes and at the same time lowered blood triacylglycerols and glucose level. Considering the equal content of ellagitannins in both supplemented diets, it may be speculated that the above effects were due to the presence of proanthocyanidin fraction.